Effect of breathing relaxation on stress related to COVID-19 pandemic among older adults in nursing homes: A pre-experimental study - Betan, Yasinta; Jenau, Benedikta; Djogo, Herliana Monika Azi; Rumbo, Helmi (Jurnal Keperawatan Padjadjaran, 2024)
Background: Elderly in nursing homes are facing more mental health consequences due to the COVID-19 pandemic situation. Assessment of the appropriate intervention in declining the level of stress-related to pandemic situations among institutionalized elderly is critical. Purpose: this study was conducted to evaluate the effectiveness of breathing relaxation on stress related to the COVID-19 pandemic among elderly people in nursing homes. Methods: a quasi-experimental with a one-group pretest-posttest design was used in the present study. Thirty elderlies were recruited using the purposive sampling method. Perceived Stress Scale (PSS-10) related to COVID-19 was used to identify the level of stress among the elderly. Twenty minutes of breathing relaxation were conducted once a day for 1-week from January 6 to January 12, 2021. The intervention was taught and guided by the researcher in small groups of 5-7 elderly based on the number of residents in the homesteads. Results: Of 30 participants, 60% were female, and the mean age was 72.80 (SD=8.50) years. The average length of stay in the nursing home was 8.10 (SD=8.75) years. The elderly in nursing homes who performed breathing relaxation once a day for one week significantly decreased their stress related to the COVID-19 pandemic (t = 4.881, Ï = .000). Conclusion: The current study highlights the significance of breathing relaxation in relieving perceived stress related to COVID-19 pandemic. This intervention is useful in daily practice for improving the psychological well-being of the elderly, especially in a pandemic situation.